REGENERATION CHARACTERISTICS OF BURN WOUNDS OF THE PRESERVATION GEL OF THE FIELD BINDWEED EXTRACT - Yakubova Umida Bakhtiyarovna (Scholar Express Journals, 2024)
Currently, in the arsenal of doctors there is a large selection of drugs with regenerative and reparative properties. However, none of them are universal and their effectiveness is far from optimal. This necessitates the search and development of new drugs for the treatment of burn injuries.
Keywords: Medicinal plant; flavonoids; ibuprofen; burns